The sweet spot of a cricket bat for low speed impacts - Bower, R. (Sports Engineering, 2012)
The impact location of a cricket ball on a cricket bat has a large influence on the resulting rebound velocity of the ball. To measure this, a cricket bat was swung in a pendulum motion towards a cricket ball suspended in space. The position of the ball was modified so that it impacted the bat at 24 different positions on the face of the bat. This included six positions longitudinally and four positions laterally. The speed of the bat and each rebound were measured by a radar gun so that the apparent coefficient of restitution (ACOR) could be calculated. Impacts occurring centrally and 1 cm either side of the midline produced significantly higher rebound speeds and ACOR`s than impacts occurring 2 and 3cm off centre (p < 0.01). Impacts occurring 15-20 cm from the base of the bat produced the highest rebound speeds (p < 0.01) and impacts occurring 20-30 cm from the base of the bat produced the highest ACOR values. Implications for higher speed impacts and game scenarios are discussed.